NEAREST NEIGHBOR ANALYSIS OF BALI’S EDUCATIONAL FACILITIES DISTRIBUTION AND SPATIAL POLICY COMPLIANCE - Dani Lukmito Utomo (Badan Perencanaan Pembangunan Daerah Kabupaten Sleman, 2026)
Spatial inequality in educational facilities and their non-compliance with spatial planning remain critical challenges in rapidly developing regions such as Bali. However, research integrating spatial distribution pattern analysis with compliance assessment against the Regional Spatial Plan (Rencana Tata Ruang Wilayah/RTRW) remains limited. This study analyzes the spatial distribution patterns of educational facilities in Bali Province and evaluates their compliance with the RTRW. Employing a quantitative approach with spatial analytical design, this study utilized secondary data on educational facilities and RTRW spatial pattern data. Distribution pattern analysis employed the Average Nearest Neighbor (ANN) method with z-score significance testing (p < 0.05), while compliance evaluation was conducted using spatial overlay techniques. The results reveal that all regencies and the city in Bali Province exhibit statistically significant clustered distribution patterns (ANN < 1, p < 0.001). Buleleng Regency demonstrates the most intensive clustering (ANN = 0.463445), while Denpasar City approaches a random pattern (ANN = 0.856465). Compliance evaluation reveals that 55.75% of facilities are appropriately situated in Residential Zones, while 44.25% occupy non-suitable zones, including Agricultural Zones (14.10%), Tourism Zones (5.46%), as well as Protected Areas and Defense and Security Zones. These findings highlight systemic spatial inequities and gaps between planning policy and implementation, driven by historical factors, urbanization pressures, and weak spatial planning law enforcement. This research recommends evidence-based RTRW revision, strengthening of spatial utilization control mechanisms, and integration of community participation.